The Effect of Participation in 17th August Competitions on Students' Physical Fitness: A Cross-Sectional Study - Haddina, Elisa; Amri, Annisa Dwi; Sihombing, Abdi Trinitatis; Zebua, Aland Pelita Teoli; Batubara, M. Bayu Samudra; Ahmad, Nukhi Hotma Partahanan (CV. INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: The 17th August Independence Day celebrations in Indonesia have traditionally incorporated competitive sports events designed to foster national pride and patriotic spirit. However, limited empirical evidence exists examining the relationship between participation in these competitions and objective measures of physical fitness among students. This study aimed to investigate the effect of participation in 17th August traditional competitions on students' physical fitness levels, comparing active participants with non-participants across multiple fitness dimensions. Materials and methods: A cross-sectional comparative study was conducted with 248 secondary school students (aged 13-17 years; 124 participants, 124 non-participants) in Jakarta, Indonesia. Physical fitness was assessed using standardized tests including cardiorespiratory endurance (VO₂ max estimation), muscular strength (sit-ups and push-ups), flexibility (sit-and-reach test), speed (50-meter dash), and agility (shuttle run). Participants completed a structured questionnaire documenting competition participation history. Statistical analysis employed independent samples t-tests, ANCOVA, and linear regression analysis. Results: Students who participated in 17th August competitions demonstrated significantly superior physical fitness across multiple measures compared to non-participants: cardiorespiratory endurance (M = 38.2 vs. 32.1 mL/kg/min, p < 0.001), one-minute sit-ups (M = 32.4 vs. 28.7 repetitions, p = 0.002), flexibility (M = 15.3 vs. 12.8 cm, p < 0.001), and speed performance (M = 8.2 vs. 8.9 seconds for 50-meter dash, p = 0.001). Effect sizes ranged from small to moderate (d = 0.42 to 0.82). Participation in multiple events (≥3 activities) produced greater fitness improvements (β = 0.58, p < 0.001) than single-event participation. Conclusions: Participation in 17th August traditional competitions is positively associated with enhanced physical fitness in adolescent students. These culturally embedded competitive events show promise as practical vehicles for promoting youth physical activity and fitness while fostering national cultural values. Future longitudinal studies should examine long-term fitness trajectories and identify mechanisms sustaining physical activity post-event.